Jalan Salib sebagai Dasar Pendidikan Kristen: Upaya Mengimplementasikan Pendidikan Kristen dalam Realitas Sosial di Indonesia - Firman Panjaitan (Harati: Jurnal Pendidikan Kristen, 2024)
This study intends to analyze the role of Christian education to the existing social reality, especially the problem of poverty and injustice, in Indonesia. The problem of poverty and injustice in Indonesia is a problem that must be considered. Therefore, educational institutions, especially Christian education, should be able to develop a form of education that is not just make smart learners intellectually (only transfer of knowledge) but is able to provide intelligence holistically, so that learners have intelligence as well as sensitivity to existing social situations. By using qualitative methods, with the approach of literature studies, this study resulted in a conclusion that Christian education should foster contextual spirituality which is based on the way of the cross, because the way of the cross opens up new perspectives for suffering with everyone who suffers. Thus the way of the cross, as a contextual spirituality, opens awareness and fosters empathy to engage directly in every social reality in Indonesia, thus creating efforts to minimize suffering due to poverty and injustice.